2013
DOI: 10.1097/ijg.0b013e3182447d9b
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Risk Factors and Glaucomatous Damage in Untreated Primary Open-angle Glaucoma

Abstract: Despite small differences between the morphologic and functional glaucomatous damage, IOP and perfusion parameters seem to contribute, at least in part, independently to both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Previous histopathological [6,7]. The ocular flowmetry studies concluded that diminished ocular perfusion is included in the pathogenesis of glaucoma [5,25]. Moreover, recent researches emphasized that subfoveal choroidal blood flow was also reduced parallel with the ocular blood flow in glaucoma patients [5,25,26].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous histopathological [6,7]. The ocular flowmetry studies concluded that diminished ocular perfusion is included in the pathogenesis of glaucoma [5,25]. Moreover, recent researches emphasized that subfoveal choroidal blood flow was also reduced parallel with the ocular blood flow in glaucoma patients [5,25,26].…”
Section: Discussionmentioning
confidence: 97%
“…The ocular flowmetry studies concluded that diminished ocular perfusion is included in the pathogenesis of glaucoma [5,25]. Moreover, recent researches emphasized that subfoveal choroidal blood flow was also reduced parallel with the ocular blood flow in glaucoma patients [5,25,26]. In patients with glaucoma, decreased choroidal blood flow was clinically demonstrated, and it was associated with diminished central retinal function based on automated perimetry and pattern electroretinographic measurements [26].…”
Section: Discussionmentioning
confidence: 97%
“…Higher intraocular pressure (IOP) at baseline and greater IOP fluctuation are strong risk factors for glaucoma, although only a limited subset of individuals with ocular hypertension (OHT) will develop this disease 2. More recent data suggested that, often, visual field deterioration occurs despite IOP control, stimulating research that demonstrated that low cerebral spinal fluid pressure,3 sleep apnoea,4 blood flow alteration5 and reduced perfusion pressure6 are relevant determinants of the demise of retinal ganglion cells in glaucoma. How each of the suspected risk factors may contribute to the specific features of glaucomatous neuropathy is subject of intensive research.…”
Section: Introductionmentioning
confidence: 99%
“…8 Abnormal choroidal blood supply is likely to contribute to the pathogenesis of glaucomatous optic neuropathy. 9 Resistance to flow is related to the diameter of a vessel 10 ; thus, choroidal thickness (CT) may be proportional to the blood flow in the choroid and may be an important metric for choroidal health.…”
mentioning
confidence: 99%